PERAN MAHKAMAH INTERNASIONAL DALAM PENYELESAIAN SENGKETA PELANGGARAN TERITORIAL - Dewa Ayu Diah Ambarawati; Ni Putu Rai Yuliartini; Komang Febrinayanti Dantes (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
Territorial borders in a country is one proof that the country is already independent and has been recognized internationally. However, from direct observation as part of the international community, I feel that some are still experiencing disputes related to this territorial issue, especially from the issue of maritime territorial violations. So in resolving these disputes peacefully without any violence, especially in achieving world peace and order, it is necessary to have the role of courts run by the International Court of Justice under the auspices of the United Nations. This paper will explain further and in depth about the role of the International Court of Justice in resolving disputes over territorial violations.